Flatfoot decreases school functioning among children < 11 years of age - Damayanti, Yuke; Hadisoemarto, Panji Fortuna; Defi, Irma Ruslina (Faculty of Medicine, Trisakti University, 2018)
Background Flatfoot is a musculoskeletal abnormality commonly found in children that could result in a reduction of quality of life because of its related symptoms and functional abnormalities. This study aimed to determine the association between flatfoot and the quality of life among children 5-18 years of age. Methods A cross sectional design was used in this study of children aged 5-18 years. The diagnosis of flatfoot was made in accordance with the Chippaux-Smirak Index classification, whereas general and domain-specific quality of life were measured using the Indonesian version of PedsQL™ that has been previously validated. Mann Whitney test was used to compare quality of life between children with flatfoot and normal feet, along with other variables that potentially may influence a child’s quality of life. Results A total of 79 out of 120 subjects was used to analyze the data. There was a statistically significant difference in the quality of life score in the school functioning domain between children with flatfoot (64.46 ±18.22) and those with normal feet (75.90 ±17.29) in children <11 years of age (p=0.029). Apart from this, the study did not find any statistically significant differences in the total quality of life score or in other quality of life domains between the two groups. Conclusions Flatfoot significantly decreases children’s quality of life in the school functioning domain. Early detection and correction of flatfoot may be necessary to improve the educational attainment of children suffering from this condition.